ผลของโปรแกรมการจัดการความเจ็บปวดด้วยการดูดนมแม่ต่อการตอบสนองความเจ็บปวดในทารกแรกเกิดที่ได้รับการเจาะหลอดเลือดดำ - ขวัญนุช พชระวรางกูร (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The purpose of this quasi-experimental study was to examine the effect of pain management program by breastfeeding on pain response in newborn undergoing venipuncture. The subjects were 40 newborns, gestational age of 38-40 weeks, admitted to the sick newborn ward. The control group received routine nursing care while the experiment group received the pain management program by breastfeeding. The experimental pain management program by breastfeeding was tested for content validity. Data collection instrument, the neonatal infant pain scale, was validated by the back-translation technique and had the Cronbach’s alpha reliability of .89. Data were analyzed by descriptive statistics, independent t-test and repeated measures ANOVA with a Scheffe’s correction for multiple comparison. Major findings were as follow: 1.The experiment group had significantly lower pain responses at p < .05 on thephysiological dimension to venipuncture at all compared minutes for heart rate but not for oxygen saturation. The mean difference of the heart rate at the 2nd minute was lower than the 1st, the 3rd was lower than the 2nd, and the 3rd was lower than the 1st. The mean difference of oxygen saturation at 3rd minute was lower than the 1st. The experiment group had significantly lower pain responses at p < .05 on the behavioral responses to venipuncture at all compared minutes. The mean score of behavioral responses at the 2nd minute was lower than the 1st, the 3rd was lower than the 2nd and the 3rd was lower than the 1st. 2.Comparative between groups showed that the mean differences of the heart rate and oxygen saturation in the experimental group were lower than those of the control group at the 2nd and 3rd minutes (p < .05). The mean scores of behavioral responses in the experimental group were lower than those of the control group at all minutes of comparison (p < .05).